Text Mining dengan K-Means Clustering pada Tema LGBT dalam Arsip Tweet Masyarakat Kota Bandung - Eko Yulian (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2018)
The movement of LGBT is growing rapidly through social media so that LGBT ideas can be freely expressed. The tweeter is one of the media that is often used for that purpose. Comments or